The limited value of triage vital signs in predicting influenza infection in children aged 5 years and under in the emergency department: A single-center retrospective cross-sectional study. Issue 44 (5th November 2021) - Lam, Rex Pui Kin; Chan, Kin Ling; Cheung, Arthur Chi Kin; Wong, Kin Wa; Lau, Eric Ho Yin; Chen, Lujie; Chaang, Vi Ka; Woo, Patrick Chiu Yat
Abstract : Abstract: Diagnosing influenza in children aged 5 years and under can be challenging because of their difficulty in verbalizing symptoms. This study aimed to explore the value of the triage heart rate (HR), respiratory rate (RR), and temperature, either alone or when combined with individual symptoms and signs, in predicting influenza infection in this age group. This was a retrospective study covering 4 influenza seasons from 2017 to 2019 in an emergency department (ED) in Hong Kong. We recruited patients ⩽5 years of age who had an reverse transcription polymerase chain reaction influenza test within 48 hours of ED presentation. The diagnostic performance of the triage HR, RR, and temperature was evaluated as dichotomized or categorized values with diagnostic odds ratios (DORs) calculated based on different age-appropriate thresholds. Linear discriminant analysis was performed to assess the combined discriminatory effect of age, HR, RR, and temperature as continuous variables. Of 322 patients (median age 26 months), 99 had influenza A and 13 had influenza B infection. For HR and RR dichotomized based on age-appropriate thresholds, the DORs ranged from 1.16 to 1.54 and 0.78 to 1.53, respectively. A triage temperature ≥39.0 °C had the highest DOR (3.32) among different degrees of elevation of temperature. The diagnostic criteria that were based on the presence of fever and cough and/or rhinitis symptoms had a higher DOR compared with the Centers for Disease Control and Prevention influenza-like illness criteria (4.42 vs 2.41). However, combining HR, RR, or temperature with such diagnostic criteria added very little to the diagnostic performance. The linear discriminant analysis model had a high specificity of 92.5%, but the sensitivity (18.3%) was too low for clinical use. Triage HR, RR, and temperature had limited value in the diagnosis of influenza in children ⩽5 years of age in the ED. Fever and cough and/or rhinitis symptoms had a better diagnostic performance than the Centers for Disease Control and Prevention influenza-like illness criteria in predicting influenza in this age group. Abstract : Supplemental Digital Content is available in the text